Gong dan Genderang dalam Liturgi Wajah Inkulturasi Gereja di Tanah Timor - Venidora Palbeno; Intansakti Pius X; Emmeria Tarihoran (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The use of gongs and drums in the liturgy of the Catholic Church in Timor is a tangible form of inculturation, which is a process of dialogue between faith and local culture that enriches the spiritual experience and strengthens the identity of the people. Gongs and drums, which in Timorese culture have a symbolic meaning as a means of communication with ancestors and a marker of unity, are presented in the liturgy as a means of spiritual and cultural expression, making the liturgy a meeting space between tradition and faith. This process not only adds an aesthetic dimension, but also deepens the spiritual appreciation of the people and strengthens the liturgical communion. However, inculturation also brings theological and pastoral challenges, such as the risk of syncretism and cultural abuse, so adequate pastoral assistance and liturgical education are needed in order for the process to maintain the integrity of the faith and the values of the liturgical screen. Thus, inculturation is carried out wisely as a means of establishing faith, strengthening the identity of the local Church, and deepening the spiritual experience of the people in the land of Timor.